2017
DOI: 10.1111/beer.12156
|View full text |Cite
|
Sign up to set email alerts
|

Sense and sensibility: Testing an attention‐based view of organizational responses to social issues

Abstract: According to attention-based theories, to explain organizational attention is to explain organizational behavior. In our study, we test the model of situated attention and firm behavior by examining the effects of attention structures and allocation of attention on organizational outcomes. We hypothesize a positive relationship between attention structures and the allocation of organizational attention that, in turn, has an effect on financial performance. Using a unique data set composed of indicators of soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Extant literature has used several different measures for performance, for example, Gómez-Bezares, Przychodzen, and Przychodzen (2017) examine the impact of CSR activities on financial performance. Similarly, Ferreira (2017) observed that CSR activities influenced the financial performance of organizations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Extant literature has used several different measures for performance, for example, Gómez-Bezares, Przychodzen, and Przychodzen (2017) examine the impact of CSR activities on financial performance. Similarly, Ferreira (2017) observed that CSR activities influenced the financial performance of organizations.…”
Section: Discussionmentioning
confidence: 94%
“…Extant literature has used several different measures for performance, for example, Gómez‐Bezares, Przychodzen, and Przychodzen () examine the impact of CSR activities on financial performance. Similarly, Ferreira () observed that CSR activities influenced the financial performance of organizations. Relationship between CSR activities and mutual wellbeing of MNE and host market has been also widely examined in the EM context (Forcadell & Aracil, ).…”
Section: Research Context and Methodologymentioning
confidence: 91%
“…There is a relationship between corporate philanthropy practices, but when we consider them separately, management through foundations is determinant in the market value, and management through donations is not. Management through foundations is thought to be integrated into the firm strategy (Brammer et al, ) and evaluated by the investor as a signal of consistency (Ferreira, ), credibility, and professionalism, and it favours transparency (Abdelmotaal & Abdel‐Kader, ; Bereskin et al, ), affecting market value positively.…”
Section: Discussionmentioning
confidence: 99%
“…Management through foundations is thought to be integrated into the firm strategy (Brammer et al, 2006) and evaluated by the investor as a signal of consistency (Ferreira, 2017), credibility, and professionalism, and it favours transparency (Abdelmotaal & Abdel-Kader, 2016;Bereskin et al, 2016), affecting market value positively. The relationship between foundations and market value highlights the importance of integrating philanthropy within the core business (Zerbini, 2017) rather than using sporadic practices (Chen et al, 2008) to affect the firm's market value.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 1 more Smart Citation